Assessment of Modern Trends in the Development of Accumulative Pension Schemes in the Russian Federation - Yulia Y. FINOGENOVA (Communications of International Proceedings, 2020)
The paper discusses the possible transformation of the existing accumulative pension system in Russia, taking into account the concept of the guaranteed pension plan (GPP) announced by the Government at the end of 2019. The main difficulties of transition to the concept of GPP, taking into account the peculiarities of savings strategies of Russian citizens, are presented. The analysis of existing strategies for investing pension assets in mandatory and voluntary pension systems in Russia is carried out. As well as an analysis of foreign experience of pension savings’ investment. The main ways of reforming the accumulative pension system are shown, as well as approaches to forming the structure of the investment portfolio of non-state pension funds are proposed.
Keywords: Non-state pension funds; guaranteed pension plan; pension assets investments strategies; compulsory pension assets allocation; voluntary pension assets allocation.